Older age is associated with a distinct and marked reduction of functionality of both alloreactive CD4+ and CD8+ T cells - Litjens, Nicolle H. R.; van der List, Amy C. J.; Klepper, Mariska; Reijerkerk, Derek; Prevoo, Fréderique; Betjes, Michiel G. H. (Frontiers in Immunology, 2024)
Older recipient age is associated with a significant decreased risk for rejection after kidney transplantation which is incompletely understood. In a longitudinal study, circulating alloreactive T cells were assessed of young (≤45 years) and older (≥55 years) stable kidney transplant recipients. Alloreactive T-cells were identified by CD137-expression and phenotype, cytokine producing and proliferative capacity, were evaluated using multiparameter flowcytometry. The results show that before transplantation frequencies of alloreactive CD4+ and CD8+ T-cells in older KT-recipients are significantly higher and shifted towards an effector memory-phenotype. However, the frequency of polyfunctional (≥2 pro-inflammatory cytokines) CD4+ T-cells was significantly lower and less IL2 was produced. The frequency of polyfunctional alloreactive CD4+ T-cells and proliferation of alloreactive T-cells donorspecifically declined after transplantation reaching a nadir at 12 months after transplantation, irrespective of age. A striking difference was observed for the proliferative response of alloreactive CD8+ T-cells. This was not only lower in older compared to younger recipients but could also not be restored by exogenous IL2 or IL15 in the majority of older recipients while the response to polyclonal stimulation was unaffected. In conclusion, older age is associated with a distinct and marked reduction of functionality of both alloreactive CD4+ and CD8+ Tcells.